Marketing strategy for small- to medium-sized manufacturers a practical guide for generating growth, profit, and sales - France, Charles E. (2013 digital library., 2013)
Small and medium manufacturers' attempts to grow their business often produce less-than-desired results due to self-inflicted obstacles and pitfalls that defeat their well-intended efforts. Many do not follow generally accepted basic business practices such as knowing product costs and margins, obtaining strategically useful information about customers, conducting market research to identify prospective customers, and understanding competitors' advantages and disadvantages needed to build effective growth strategies. Their approach to pursuing growth strategies--a.k.a shotgun marketing--is akin to ready, shoot, aim--and often the business' working capital, cash flow, financial ratios, and overall profitability are insufficient to afford the costs of needed sales, marketing, and promotional strategies typically called for to find and develop new customers, markets, and products.